Determinants of Electricity Consumption in Indonesia - Ayasyifa, Shannay (Jurnal Ilmu Ekonomi Terapan, 2022)
Electrical energy is one energy source that plays an essential role in human life daily, such as industrial, commercial, government, and household activities. All processes related to public activities can dash effectively and efficiently with electricity. The electricity consumption in Indonesia has reportedly increased every year. This enhancement can be caused by several factors, one of which is the population. The increasing electricity consumption in Indonesia has shown that electricity is the primary driving sector for the development that supports productivity and public activities. It is hoped that the economy will also increase. Based on this statement, this study aimed to analyze the factors which affect electricity consumption in Indonesia during the 2015 – 2019 period. This study used secondary data by taking four independent variables, including GDRP per capita, population, installed power capacity, and electricity tariffs. The dependent variable used in this study is electricity consumption. The research used the estimation technique of the Fixed Effect Model, which was selected based on the result of the Chow Test. The results in the regression analysis showed that the GDRP per capita and population variable both resulted in positive and insignificant effects on the electricity consumption in Indonesia during the 2015 – 2019 period. The installed power capacity variable had a positive and significant influence on the electricity consumption in Indonesia during the 2015 – 2019 period. Meanwhile, the electricity rate variable had a negative and insignificant effect on the electricity consumption in Indonesia during the 2015 – 2019 period.